ASYNCHRONOUS BRAIN CONTROLLED WHEELCHAIR MOBILITY FOR DISABLED PEOPLE - MOHAMED BASHIR, ELTAF ABDALSALAM (2018)
Brain computer interface (BCI), as a solution to disabled people’s concerns has drawn attention in biomedical engineering over the last decade. Findings show that a synchronous BCI system is not feasible for disabled people because the user needs to send the commands at pre-determined time specified by BCI.